Chinese professionals in Singapore : an analysis of their integration process in Singapore - Wu, Hao (2014)
Despite the extensive study on immigration and the comprehensive understanding of assmilation theory. Most of these works focus on Western country where a significant difference exists between mainstream locals and foreigners. This paper attempts to analysis the situation when both mainstream locals and foreigners are arguably from similar cultural background. This will be use to further the understanding on the interactive process between host country and foreign guests, as well as expanding on the existing study of dominant subordinate group relation.